Hemodynamic Effects of Left Upper Extremity Arteriovenous Fistula on Ipsilateral Internal Mammary Coronary Artery Bypass Graft - Coskun, Isa; Colkesen, Yucel; Altay, Hakan; Ozkan, Ugur; Demirturk, O. Saim; Gulcan, Oner; Guvener, Murat (The Thoracic and Cardiovascular Surgeon, 2013)
Objective Arteriovenous fistula (AVF) in patients undergoing hemodialysis (HD) may cause coronary left internal mammary artery (IMA) steal. This phenomenon was demonstrated by few prospective studies with limited number of patients and case reports. We aimed to demonstrate with a relatively larger patient population that the AVF may cause ipsilateral IMA steal.Methods We included 22 prospective patients undergoing HD who had left IMA to left anterior descending artery graft and left upper limb AVF. Right IMA was taken as control. Flows were assessed by using color Doppler ultrasonography.Results The mean age was 57.8 ± 9 years. Statistically nonsignificant increases in AVF flow and decreases in left IMA flow were observed during HD compared with pre-HD. Moreover, fistula localization did not affect median left IMA flows (for peak systolic velocity [PSV] 43.7 versus 70 cm/s, respectively; p = 0.7, and for end diastolic velocity [EDV] 3.4 versus 6.5 cm/s, respectively; p = 0.7). We have not detected significant difference in left IMA flows during HD (median values of PSV 58.4 versus 68.4 cm/s, respectively; p = 0.1, and EDV 6.4 versus 4.4 cm/s, respectively; p = 0.08). Only three patients experienced dialysis-induced reduction of ipsilateral IMA flow that was accompanied by evidence of hypokinesia of the anterior left ventricular wall without clinical angina.Conclusions Hemodynamically affected left IMA flow by ipsilateral upper extremity AVF may cause steal phenomenon. Hemodynamic differences between left and right IMAs in patients undergoing HD via left wrist and brachial fistulae are limited.
Keywords: hemodialysis; arteriovenous fistula; coronary steal; coronary bypass surgery